2022
DOI: 10.1002/admt.202101392
|View full text |Cite
|
Sign up to set email alerts
|

Application of a c‐Si Solar Cell with a Three‐Dimensional Structure to Indoor Photovoltaics

Abstract: are considerably weaker sources of illumination compared to sunlight.Unfortunately, most PV devices are optimized for outdoor use, having the ability to generate electric power on the order of watts to gigawatts (e.g., power plants) with sunlight exposure. [14] The crystalline silicon (c-Si) solar cell has been widely used under sunlight, as it is economical, expandable, and capable of being mass-produced. [15][16][17] However, artificial light sources have low light intensity and a narrow spectrum, residing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Unlike photovoltaics deployed outdoors, indoor photovoltaics operate with low-intensity and dispersed light sources. 13,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]70 In general, the indoor light intensity is less than 1/100th the intensity of sunlight. The spectrum also differs from that of sunlight and depends on the kind of lighting.…”
Section: Sustainable Energy and Fuelsmentioning
confidence: 99%
“…Unlike photovoltaics deployed outdoors, indoor photovoltaics operate with low-intensity and dispersed light sources. 13,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]70 In general, the indoor light intensity is less than 1/100th the intensity of sunlight. The spectrum also differs from that of sunlight and depends on the kind of lighting.…”
Section: Sustainable Energy and Fuelsmentioning
confidence: 99%
“…22,[28][29][30][31][32] Interestingly, recent studies have shown that emerging photovoltaic technologies such as perovskite solar cells (PSCs), [33][34][35] OSCs, 25,28,36 and dye-sensitized solar cells (DSSCs) [37][38][39] are better for converting indoor light into electricity than other inorganic Si, CIGS technologies. [40][41][42] This is due to a broader range of optical tunability, a higher absorption coefficient, and smaller leakage currents at low light intensities. 7,[43][44][45][46] For example, the PSCs had a PCE of 37.2% under 6500 K LED illumination (1000 lux) with ambient stability of more than 800 hours reported, as by Noh and workers.…”
Section: Hemraj Dahiyamentioning
confidence: 99%
“…For applications in devices such as photovoltaics, photodetectors, and light-emitting diodes, group III–V direct band gap semiconductors and bulk Si are widely used in conventional diode structures. However, these materials lack flexibility and transparency and have low optical absorption coefficients, limiting their applications in flexible devices like solar cells or transparent displays. Unlike ordinary semiconductors, there has been considerable interest in the utilization of two-dimensional (2D) layered materials, such as transition metal dichalcogenides (TMDs), for the fabrication of high-performance PV devices. TMDs exhibit advantageous photovoltaic properties owing to their wide range of band gaps, indicating the wavelengths of light that the materials can absorb and convert into energy.…”
Section: Introductionmentioning
confidence: 99%